Prekäre Räume – prekäre Subjekte - Betscher, Silke (My University, 2018)
The establishment of so-called AnKER-centers for refugees is important in the recent political debate. As places of „organized disintegration“, they take all aims of a welcome culture, which dominated the verbal discourse in 2015 and 2016, to absurdity. With the help of a visual discourse analysis of press pictures in German media, this article investigates spatial representations on refugees and forced migration in relation to the subject positions evoked by the images. The photographs of refugees and refugee accommodation can be understood as a materialization of othering and socio-cultural exclusion. The visual discourse permanently repeats the living of refugees as non-dwelling and thus negates the affiliation of refugees in a collective of civic subjects. It is argued that despite a verbal discourse celebrating a „Willkommenskultur“, the visual discourse normalized forms of spatial exclusion at the very same time.
provisorische Behausungen und verwaltete Räume in visuellen Diskursen der Tagespresse zu Flucht und Asyl
Keywords: 300 Sozialwissenschaften